2017
DOI: 10.3961/jpmph.17.036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Subjective Life Expectancy: Comparison With Actuarial Life Expectancy

Abstract: ObjectivesSubjective life expectancy (SLE) has been found to show a significant association with mortality. In this study, we aimed to investigate the major factors affecting SLE. We also examined whether any differences existed between SLE and actuarial life expectancy (LE) in Korea. MethodsA cross-sectional survey of 1000 individuals in Korea aged 20-59 was conducted. Participants were asked about SLE via a self-reported questionnaire. LE from the National Health Insurance database in Korea was used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Authors also confirmed the disparity in ILE between different levels of economic status as has been shown in other studies. Similarly, SLE also increased more in the high-income group than in the low-income group in another study [38]. Therefore, targeted intervention programs are needed for vulnerable subgroups of individuals, including those with low socioeconomic status level.…”
Section: Discussionmentioning
confidence: 92%
“…Authors also confirmed the disparity in ILE between different levels of economic status as has been shown in other studies. Similarly, SLE also increased more in the high-income group than in the low-income group in another study [38]. Therefore, targeted intervention programs are needed for vulnerable subgroups of individuals, including those with low socioeconomic status level.…”
Section: Discussionmentioning
confidence: 92%
“…In 2050, that number is predicted to be more than 3,000,000. 7 As the general population ages, there will be an increasing number of vascular patients aged 90s and older.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset also contains some socioeconomic variables that include gender, age, employment status, and living conditions From this dataset, we extracted information about all individuals aged 50 to 65 to target elderly populations. We included a comprehensive list of independent variables informed by the literature [13,14]. These variables were categorized into seven groups of variables: sociodemographic, economic, comorbidities, behavioral, quality of life, living conditions, and genetic information.…”
Section: Datamentioning
confidence: 99%